Formulation of Lerak Extract (Sapindus rarak DC) and Aloe Vera Extract (Aloe vera Linn) as Paper Hand Soap: Application of Factorial Design - Margaretta Berlinda Listyawati; Ni Putu Aryaswari Putri; Dina Christin Ayuning Putri (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
Soapberry contains saponin compounds and can be used as a surfactant in a soap. Aloe leaves contain lignin compounds as an emollient. Soapberry extract and aloe extract can be formulated into paper hand soap. This study aims to determine the optimum composition of soapberry extract and aloe extract in paper hand soap formulation. Quasi-experimental research was conducted using a 2-factor and 2-level factorial design. Physical property tests were done including organoleptic tests, pH, washing time, moisture content, foam height, reduction in Trans Epidermal Water Loss (TEWL) values and freeze-thaw physical stability tests. Data analysis used Design Expert version 13 (free-trial version) software with a two-way ANOVA test and 95% confidence level. The overlay plot obtained was used to determine the optimum composition area. The results found that the combination of soapberry extract and aloe extract had an effect on physical properties in the form of foam height and reduced TEWL and the optimum formula composition for soapberry extract was 63.5224 grams and aloe extract was 20.1866 grams.